Optimizing the Construction of the NUWSP SPAM Piping Network in Gresik Regency - Abdul Latif; Maritha Nilam Kusuma (Journal of Civil Engineering, Planning and Design, 2023)
Water is essential for all living things, including humans. Water, both in terms of quality and quantity, will have an effect on human life. The Indonesian government is preparing the National Urban Drinking Water Supply Plan (NUWSP) with assistance from the World Bank. A significant portion of the Bank's financial resources are allocated to technical assistance and capacity building in support of the Indonesian government's infrastructure expenditures in all urban water distribution platforms. The NUWSP Work was implemented during an 11-month period, from November 18, 2021 to August 22, 2022, with the NUWSP Work Location at Gresik Regency in East Java. During the data collection stages, both primary and secondary data were obtained. The drinking water supply system (SPAM) planning stage comprises calculating BOQ and RAB, as well as DED for drinking water, and planning for the drinking water JDU system. The contractor takes measurements and standards before installing a field-specific bow plank at the tying point. To avoid pipe damage, individual pipe fittings must be lowered into the trench using the right equipment. The volume of excavation is computed using a depth of 180 cm, a breadth of 60 cm, and a length of excavation of 31 km from six pieces of a pipeline. The Bill of Quantity (BOQ) and Budget Plan (RAB) necessary to complete the SPAM pipeline network work in Gresik Regency were IDR 27,823,590,000.00, based on the results and discussion of the Optimization of SPAM Network Work (NUWSP) in Gresik Regency.